Association of newly replicated DNA with the nuclear matrix of Physarum polycephalum. - Hunt, B F (1981)
We have studied the role of the nuclear matrix in DNA replication in a naturally synchronized eucaryote, Physarum polycephalum. When P. polycephalum. When P. polycephalum macroplasmodia were pulse labeled with 3H-thymidine, the DNA remaining tightly associated with the matrix was highly enriched in newly synthesized DNA. This enrichment was found both in nuclei that had just initiated DNA replication as well as in nuclei isolated later during S phase. Pulse chase experiments showed that the association of newly replicated DNA with the matrix is transient, since most of the newly replicated DNA could be chased from the matrix by incubating pulse labeled macroplasmodia in media containing unlabeled thymidine. Studies measuring the size distribution of the matrix DNA supported the hypothesis that replication forks are attached to the nuclear matrix. Reconstitution controls indicated that these results were unlikely to be due to preferential, nonspecific binding of nascent DNA to the matrix during the extraction procedures. These results with P. polycephalum in combination with previous studies in non-synchronized rodent cells, suggest that the association of newly replicated DNA with the nuclear matrix may be a general feature of eucaryotic DNA replication.